Improved Performance of ELISA and Immunochromatographic Tests Using a New Chimeric A2-Based Protein for Human Visceral Leishmaniasis Diagnosis - Maria Marta Figueiredo; Anna R. R. dos Santos; Lara C. Godoi; Natália S. de Castro; Bruno C. de Andrade; Sarah A. R. Sergio; Selma M. B. Jerônimo; Edward J. de Oliveira; Ruth T. Valencia-Portillo; Lucilândia M. Bezerra; Hiro Goto; Maria C. A. Sanchez; et al. (Journal of Immunology Research)
Summary. Human visceral leishmaniasis (VL) is a major public health problem worldwide, leading to significant mortality rates if not properly treated and controlled. Precise identification of infected patients is essential to establish treatment and control measures. Although several VL serological diagnosis advances have been accomplished lately, mainly using recombinant antigens and immunochromatographic tests (ICTs), improvements may still be achieved using multiepitope chimeric proteins in different test platforms. Here, we reported on the evaluation of ELISA and an ICT developed with a new chimeric protein, named DTL-4, based on repetitive antigenic sequences, including those present in the A2 protein. Methods. A total of 1028 sera samples were used for the development and validation of ELISA (321 samples from L. infantum-infected patients, 62 samples from VL/AIDS coinfected patients, 236 samples from patients infected with other diseases, and 409 samples from healthy donors). A total of 520 sera samples were used to develop and validate ICT (249 samples from L. infantum-infected patients, 46 samples from VL/AIDS coinfected patients, 40 samples from patients infected with other diseases, and 185 samples from healthy donors). Findings. Using the validation sera panels, DTL-4-based ELISA displayed an overall sensitivity of 94.61% (95% CI: 89.94-97.28), a specificity of 99.41% (95% CI: 96.39-99.99), and an accuracy of 97.02% (95% CI: 94.61-98.38), while for ICT, sensitivity, specificity, and accuracy values corresponded to 91.98% (95% CI: 86.65-95.39), 100.00% (95% CI: 96.30-100.00), and 95.14% (95% CI: 91.62-97.15), respectively. When testing sera samples from VL/AIDS coinfected patients, DTL-4-ELISA displayed a sensitivity of 77.42% (95% CI: 65.48-86.16), a specificity of 99.41% (95% CI: 96.39-99.99), and an accuracy of 93.51% (95% CI: 89.49%-96.10%), while for DTL-4-ICT, sensitivity was 73.91% (95% CI: 59.74-84.40), specificity was 90.63% (95% CI: 81.02-95.63), and accuracy was 82.00% (95% CI: 73.63-90.91). Conclusion. DTL-4 is a promising candidate antigen for serodiagnosis of VL patients, including those with VL/AIDS coinfection, when incorporated into ELISA or ICT test formats.